2020
DOI: 10.3390/cosmetics7020023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chewing Training on Orofacial and Cognitive Function in Healthy Individuals: A Systematic Review

Abstract: Background: There is some evidence showing significant correlations between acute chewing gum and orofacial function, and between acute chewing gum and cognitive function; however, as far as we are aware, little is known about the chronic effects of chewing gum training on cognitive and orofacial functions in healthy adults. Objectives: To evaluate the chronic effects of chewing gum training on orofacial and cognitive functions in healthy adults. Method: Searches of the electronic databases PubMed, Scopus, BVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…is study found that the 10 m WMS in the study group at 4 and 8 weeks after intervention was obviously higher than that in the reference group (P < 0.001). Viana et al [22] pointed out in their study that postural control training combined with core muscle training was used for hemiplegic stroke patients in the recovery period, and the 10 m MWS of the patients after training was (0.69 ± 0.14) m/s, which was obviously higher than that of the conventional rehabilitation group (0.56 ± 0.13) m/s. is indicates that core muscle training can effectively improve the core trunk ability and walking ability of stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…is study found that the 10 m WMS in the study group at 4 and 8 weeks after intervention was obviously higher than that in the reference group (P < 0.001). Viana et al [22] pointed out in their study that postural control training combined with core muscle training was used for hemiplegic stroke patients in the recovery period, and the 10 m MWS of the patients after training was (0.69 ± 0.14) m/s, which was obviously higher than that of the conventional rehabilitation group (0.56 ± 0.13) m/s. is indicates that core muscle training can effectively improve the core trunk ability and walking ability of stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…The facial muscles are expected to show similar adaptations as the limb muscles, but there is a lack research to support this thesis. For the facial muscles involved in mastication, it is possible to measure maximum muscular strength and use a device for exercise training [30][31][32]. By contrast, there is no established training protocol for the muscles of the upper face [33,34].…”
Section: Effect Of Facial Exercise On Orbicularis Oculi Muscle Sizementioning
confidence: 99%